Difficulties in the study of cosmic radio noise absorption at 30 MHz using riometer at low latitude station, Kolhapur (Lat-16.8°N, Long-74.25°E) - Nikte, S.S.; Sharma, A.K.; Nade, D.P.; Rokade, M.V.; Ghodpage, R.N.; Patil, P.T.; Bhonsle, R.V. (My University, 2014)
A dual dipole antenna has been installed at low latitude station Kolhapur (Geographic 16.8°N, 74.25°E), Maharashtra, India for the study of cosmic radio noise absorption using Solid State Riometer (which operates at 30 MHz) during pre phase of 24th solar maxima. The aim for this type of study over Kolhapur was to know the response of lower (D region) ionosphere over low latitude by cosmic radio noise absorption using riometer technique during quite period as well as sudden ionospheric disturbances (SID). The observations are being taken for 3 years. Two different sites (∼40 km away from each other) were used for the installation of riometer equipment assuming minimum local noise. It is found that solar noise to cosmic radio noise hence resulting in signal saturation. The night time signal is relatively free of interference but sometimes local noise is responsible for spike-like signatures. Hence it is concluded that Kolhapur (a low latitude station) is not suitable for the study of cosmic radio noise absorption on 30 MHz with riometer and dual dipole antenna. Proper choice for operating frequency of riometer and antenna gain is suggested for low latitude use of this technique for ionospheric deviative and nondeviative absorption studies.
Keywords: Cosmic radio noise absorption; Riometer; Ionospheric absorption